2018
DOI: 10.3390/molecules23123214
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Deep Eutectic Solvents for Simultaneous Extraction of Five Aromatic Acids from Ginkgo biloba Leaves

Abstract: Ginkgo biloba leaves have various health benefits due to the presence of bioactive compounds such as polyprenyl acetates, flavonoids, and terpene trilactones. However, there is little literature reported on the aromatic acids in Ginkgo biloba leaves. In this work, five aromatic acids including shikimic acid (SA), 6-hydroxykynurenic acid (6-HKA), protocatechuic acid (PA), gallic acid (GAA), and p-hydroxybenzoic acid (PHBA) were simultaneously extracted from Ginkgo biloba leaves by employing the green deep eutec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Our expression analysis indicated that GbF3′5′H1 accumulated in the leaf at a level significantly higher than that in other tissues (except for the aging leaves after September) ( Figure 3 a), implying that this gene might play important roles in the leaf. This finding is consistent with the higher content of flavonoids in ginkgo leaves than in other tissues, and the leaf of ginkgo is the most commonly used part of the plant, with the greatest medicinal value [ 18 , 49 ]. Previous studies indicated that the mRNA transcripts of F3′5′H accumulated in the petals of Petunia hybrida and Pericallis × hybrida [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 78%
“…Our expression analysis indicated that GbF3′5′H1 accumulated in the leaf at a level significantly higher than that in other tissues (except for the aging leaves after September) ( Figure 3 a), implying that this gene might play important roles in the leaf. This finding is consistent with the higher content of flavonoids in ginkgo leaves than in other tissues, and the leaf of ginkgo is the most commonly used part of the plant, with the greatest medicinal value [ 18 , 49 ]. Previous studies indicated that the mRNA transcripts of F3′5′H accumulated in the petals of Petunia hybrida and Pericallis × hybrida [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we added water to the DES mixture to solve the viscosity problems of DES as has been conducted by several studies [ 10 , 30 , 31 ]. Our results demonstrated that water addition resulted in a lower viscosity of DES.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of the substance, especially the activity of DES, will be affected by long time extraction. Moreover, the extraction efficiency will be influenced by long-time extraction as well [ 21 , 22 ]. As a result, 30 min was considered as the best extraction time.…”
Section: Resultsmentioning
confidence: 99%